Dictapicto as a didactic resource to Increase vocabulary in students with Autism at escuela de educación básica Educa - Rosales Magallan, Arelys Stephany (2024)
The main objective of this research project was to explain the positive effect that the idactic resource Dictapicto can have on second and third-grade students with autism to increase or strengthen their vocabulary in the English language. This project investigated the problems that hinder the learning of students with ASD; among the main problems, the lack of socialization and the lack of use of didactic and visual materials stand out. Then, an analysis of how it is possible to overcome these problems through the implementation of the Dictapicto resource to develop the vocabulary of these children through visual material such as pictograms, which are ideal for children with this special educational need, was shown. This research has a qualitative approach, which took as a sample six English teachers in charge of the education of autistic children in an inclusive and private educational institution. The teachers were given questionnaires with seven questions detailing benefits, recommendations, and methodologies. The teachers surveyed gave their respective opinions on the importance of seeking different didactic resources to increase vocabulary and develop other communicative skills in the English language. The advantages of applying the didactic resource Dictapicto in teaching English to autistic students, previous teachers' experiences with their students, and suggestions on how to correctly use this resource to obtain favorable results more quickly were detailed. In conclusion, this project demonstrates that it is possi le to adapt this didactic resource knowing how to manage its use effectively.